Why Customers Stay: A Push–Pull–Mooring Perspective on Online Food Delivery Loyalty - Balqis Srikandi Wiryawan; Raditha Dwi Vata Hapsari; Radityo Putro Handrito (Penerbit Goodwood, 2026)
Purpose: This study examines the effects of service quality as a push factor and price perception of alternatives as a pull factor on customer loyalty in Online Food Delivery (OFD) services, with switching costs acting as a mooring factor within the push–pull–mooring framework. Research Methodology: This quantitative study involved 290 OFD users in Indonesia who had used at least two platforms and made at least three transactions in the last 30 days. Data were collected through an online survey and analyzed using partial least squares structural equation modeling. Results: The results show that service quality has a positive and significant effect on customer loyalty, indicating that better service performance increases users’ intention to continue using and recommending the platform. The price perception of alternatives does not significantly affect customer loyalty, suggesting that price alone does not determine loyalty in OFD services. Switching costs have a positive and significant influence on customer loyalty, meaning that perceived financial, procedural, and psychological costs of switching encourage users to remain with their current platform. The moderating role of switching costs does not strengthen the relationship between service quality and customer loyalty and does not significantly moderate the relationship between the price perception of alternatives and customer loyalty. Conclusions: Customer loyalty to OFD services is primarily driven by service quality and switching barriers rather than price considerations. Limitations: This study relied on self-reported survey data and focused on urban respondents in Indonesia. Contributions: This study extends the push–pull–mooring framework to explain customer loyalty in the OFD industry.